The Effectiveness of Digital Comic Media for Pancasila Education in Grade IV Elementary Students - Reinita,; Sarki, Melfira (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Pancasila Education is a subject that plays a significant role in shaping students' character. However, many students remain passive and are not actively involved in the learning process, which is partly due to monotonous teaching methods and overly simplistic learning media. This research aims to evaluate the feasibility of digital comic media as a learning tool to foster creative thinking, enhance problem-solving skills, and instill noble values in students' everyday lives at Class 4 of Elementary School Cluster Tanjung Emas, Tanah Datar. The research method used is Research and Development (R&D) employing the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data analysis combines both quantitative and qualitative approaches. Quantitative data is derived from the effectiveness results, while qualitative data is used to interpret these results. The findings indicate an N-Gain score of 0.42, categorizing the effectiveness as moderate. Based on these results, it can be concluded that the use of digital comic media in the learning process is effective.